WARISAN KEKERASAN DALAM PERNIKAHAN DINI: TINJAUAN TEORI CYCLE OF VIOLENCE - Ruth Stevany Luise Silitonga; Chazizah Gusnita (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The practice of early marriage is still a social issue that needs attention today. The occurrence of early marriage itself is caused by various encouragement around with the assumption that it can handle problems. In reality, early marriage is a gate to lead to new problems that are even more complex, one of which is domestic violence. Domestic violence is a long-term risk due to early marriage. The unpreparedness of couples in various aspects creates conflicts that spark acts of violence. In fact, in the field, this practice is considered normal so that it is allowed to continue to occur. Because of this form of omission, in the end the pattern of early marriage is passed down to the latest generation. This study aims to examine the background that perpetuates the practice of early marriage and becomes recurrent violence with Walker's cycle of violence theory. The research method uses descriptive qualitative and primary data collection is done by in-depth interviews with family resource persons and expert resource persons from Child Protection Agency Indonesia (LPAI). The research shows that early marriage becomes a space for violence, and the omission by the family strengthens the cycle of violence into a cross-generational legacy.